2015
DOI: 10.1016/j.conbuildmat.2015.08.034
|View full text |Cite
|
Sign up to set email alerts
|

A Raman spectroscopy study of steel corrosion products in activated fly ash mortar containing chlorides

Abstract: h i g h l i g h t sThe corrosion products were iron oxyhydroxides, goethite and lepidocrocite. Raman spectra were obtained with 532 nm and a power from 0.025 to 0.25 mW. Raman spectra were obtained with 633 nm and a power greater than 2.5 mW. For 532 nm line the phases formed were transformed into hematite at above 0.5 mW. For the line of 532 nm with 5 mW showed fluorescence. a b s t r a c tRaman spectroscopy was used to characterise the corrosion products of reinforcing steel embedded in activated fly ash mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 33 publications
0
19
0
1
Order By: Relevance
“…Raman spectroscopy is a non-destructive technique for characterization of various oxides and oxyhydroxides in steel rust [ 24 , 38 ]. It was also employed in this study to detect the phase composition of the rust in the steel samples.…”
Section: Experimental Programmentioning
confidence: 99%
See 1 more Smart Citation
“…Raman spectroscopy is a non-destructive technique for characterization of various oxides and oxyhydroxides in steel rust [ 24 , 38 ]. It was also employed in this study to detect the phase composition of the rust in the steel samples.…”
Section: Experimental Programmentioning
confidence: 99%
“…The expansion can be better understood if the rust composition is known. Criado et al [ 24 ] studied steel rust on reinforcing steel embedded in mortars containing chloride by Raman spectroscopy and found that the main corrosion products were iron with low crystallinity, α-FeOOH and γ-FeOOH. Poupard et al [ 25 ] tested steel bars in a RC beam in a marine environment by X-ray diffraction (XRD) and μ-Raman analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from these cavities, the wear track mostly resembled the coating (identified as spot C2 in figure 5d and most of the area in figure 5f) and showed strong peaks associated with oxides of Cr and Nb which could be associated with the passive layers formed on the coating surface (corrosion products sustained after evading mechanical removal). Table 2 gives the resolved peak values of the Raman spectra for the coating and the HSS specimens and the assigned phases [29][30][31][32][33][34][35][36]. Similarly, Raman spectra of the HSS wear track were also analysed to identify the corrosion products.…”
Section: Potentiostatic Conditionsmentioning
confidence: 99%
“…Raman peaks and the main oxide phases identified on the surface of the wear track[29][30][31][32][33][34][35][36].…”
mentioning
confidence: 99%
“…Surface analysis spectra were carried out with a RM 2000 Renishaw Raman microscope (Renishaw plc, Old Town, Wotton-under-Edge, Gloucestershire, UK) equipped with a laser at 633 nm with a spot diameter of 1µm and a Leica microscope coupled with an electrically refrigerated charge-coupled device (CCD) camera. The laser power was controlled at 2.5 mW in order to avoid thermal transformation [22]. Spectra were collected with 10 s of integration time and 5 accumulations to improve the signal-noise ratio.…”
Section: Micro-raman Spectroscopymentioning
confidence: 99%